Light-front description of infinite spin fields in six-dimensional Minkowski space - Buchbinder, Ioseph L. (European Physical Journal C)
We present a new 6D infinite spin field theory in the light-front formulation. The Lorentz-covariant counterparts of these fields depend on 6-vector coordinates and additional spinor variables. Casimir operators in this realization are found. We obtain infinite-spin fields in the light-cone frame which depend on two sets of the SU(2)-harmonic variables. The generators of the 6D Poincare group and the infinite spin field action in the light-front formulation are presented.